2006
DOI: 10.1103/physrevb.73.235436
|View full text |Cite
|
Sign up to set email alerts
|

Spin-current rectification in molecular wires

Abstract: We propose that spin current rectification in molecular junctions can take two different forms consistent with thermodynamic considerations: A weak form in which the spin current reverses direction when the bias applied to the junction is reversed and a strong form in which the direction of the spin current is unchanged upon reversal of the bias. We present calculations of spin-dependent transport in several molecular junctions bridging ferromagnetic ͑Fe or Ni͒ and nonmagnetic ͑Au or Pd͒ contacts and identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
76
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 42 publications
3
76
0
Order By: Relevance
“…3,22,23,24,25,26,27,28,29,30,31,32 In a step towards a more realistic description of the geometry, symmetries, and the electronic structure of particular molecules, empirical TB approaches such as the (extended) Hückel method have proved useful. 4,8,33,34,35 Based on a combination of density-functional calculations and simple phenomenological considerations, we have recently described the photoconductance of metaloligophenylene-metal junctions. 5 It was discussed how the linear-response conductance may increase by orders of magnitude in the presence of light.…”
Section: Introductionmentioning
confidence: 99%
“…3,22,23,24,25,26,27,28,29,30,31,32 In a step towards a more realistic description of the geometry, symmetries, and the electronic structure of particular molecules, empirical TB approaches such as the (extended) Hückel method have proved useful. 4,8,33,34,35 Based on a combination of density-functional calculations and simple phenomenological considerations, we have recently described the photoconductance of metaloligophenylene-metal junctions. 5 It was discussed how the linear-response conductance may increase by orders of magnitude in the presence of light.…”
Section: Introductionmentioning
confidence: 99%
“…15 It is reported that the interface states between the conduction and the electrodes dominate the transmission through the junction at moderate bias. 16 The tunneling current depends on the transition between the density of state of the metal electrode and the one side of the sample. 17,18 Under bias the energies of these interface states lock to the shifting electrochemical potentials of the contacts.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, in single gold atom junctions, T is one. When transition metals are used as electrodes, not only are they easily oxidized, but their d orbitals are used for the single atom junctions and SMJ orbitals; this means that several electron paths are used, which complicates the conductance behavior in the junction; 53,66,67 as such, gold electrodes are preferred.…”
Section: Single-molecule Analysis Methodsmentioning
confidence: 99%